Mídia e relações internacionais: diplomacia midiática no Governo Lula (2003-2010) - Burity, Caroline Rangel Travassos (2012)
This dissertation examines the international scenario characterized by new technological revolution and the global media in light with the Media Diplomacy. Based on the analysis of the context of the Information Society, it is discussed the role of the largest global networks communications in the way they are used as an instrument of control, embarrassment, intervention and negotiation in the international scenario. Foremost, there is also a discussion about international communication within the External Relations during the administration of President Lula da Silva (2003-2010), analyzing the composition of the Communication Secretariat of the Presidency (Secom/PR/PR) and its relation to the departments of the Ministry of External Relations (MRE/Itamaraty) and how politics impacted international communication strategies in Foreign Policy. For this, we used official documentary sources of the federal Government, especially available on the balance report for Foreign Policy (2003-2010), the analytical report produced by the Company's News (CDN), the report of Nation Brands Index, as well as articles of Foreign Policy, speeches, interviews, photos and events, press releases and press releases produced by MRE/Itamaraty through the "Review of Foreign Policy in Brazil." Therefore, given the data collected, it was observed that Lula da Silva used the tool of presidential diplomacy (media diplomacy) to promote the image of Brazil abroad.